Isolation and identification of Corynebacterium pseudotuberculosis from goats - Nawi, Mohd Firdaus; Saad, Mohd Zamri (2011)
The present study was conducted to isolate and identify Corynebacterium pseudotuberculosis, the causative agent of cases lymphadenitis. Five hundred goats reared in several states of Peninsular Malaysia were examined for lesions of casesous lymphadenitis. A total of six suspected goats were slaughtered and examined. Sterile cotton swabs were used to take the sample from abscesses in the affected lymph nodes. The swabs were streaked onto blood agar. Following 48 h incubation at 37C, the colonies were identified as C. pseudotuberculosis by Gramstain and polymerease chain selection (PCR).